SizweNtsalubaGobodo : managing the merger minefield - Ndaba, Zanele; Mitchell, Clare (London : Wits Business School, 2020)
It was October 2011 and Nonkululeko Gobodo, executive chair of accounting firm SizweNtsalubaGobodo (SNG), had just received the Strategy Development and Team Alignment Process Report from JvR Consulting Psychologists. The report noted that "significant effort [had] to be put into cultural alignment [of the two firms] ..., and that integration of policies, processes, systems and procedures [would] be a major task given the myriad differences." Gobodo contemplated what she and chief executive officer, Victor Sekese, should be doing to ensure a sustainable and successful merger of the two firms.
Originally Published InNdaba, Z., & Mitchell, C. (2020). SizweNtsalubaGobodo: Managing the Merger Minefield. WBS-2020-3. Johannesburg: The Case Centre, Wits Business School.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Consolidation and merger of corporations